2017
DOI: 10.1515/prolas-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Old Sweet Cherries Found in Slovak Regions and Their Preservation

Abstract: Communicated by Edîte KaufmaneThe work is focused on the evaluation of variability of morphological and pomological characteristics of several old sweet cherries (Prunus avium L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These values are lower than those reported in the literature for wild sweet cherries. Benková et al (2017) reported that fruit weight from Slovakian sweet cherries varied between 3.7 and 8.9 g ( Table 3). The Ukrainian cherries had fruit weight with range of 5.10-8.33 g (Hégedüs et al, 2013).…”
Section: Fruit and Stone Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…These values are lower than those reported in the literature for wild sweet cherries. Benková et al (2017) reported that fruit weight from Slovakian sweet cherries varied between 3.7 and 8.9 g ( Table 3). The Ukrainian cherries had fruit weight with range of 5.10-8.33 g (Hégedüs et al, 2013).…”
Section: Fruit and Stone Variabilitymentioning
confidence: 99%
“…In Spanish sweet cherry cultivars, the stalk length was reported to be varied between 30.9 and 69 mm (Pérez-Sánchez et al, 2008 and for Portuguese cultivars this parameter fluctuated between 33.4 and 49 mm (Rodrigues et al, 2008). In Iranian cultivars, Khadivi-Khub (2014) reported that fruit stalk length ranged from 23.35 to 59.44 mm and in the Latvian cherries this trait varied between 34 and 60 mm with an average of 41.55 mm (Benková et al, 2017). For the machine harvesting the longer stalk is better regarding possible damage to the fruit skin as observed in the case of short stalk.…”
Section: Fruit and Stone Variabilitymentioning
confidence: 99%
See 1 more Smart Citation